Digital solutions and development needs for workplace survey in occupational health services - Nissinen, Sari Päivikki; Sormunen, Erja; Leino, Timo (Finnish Journal of eHealth and eWelfare, 2022)
One of the main activities of occupational health services is regular workplace surveys. The purpose of workplace surveys is to investigate the hazards, exposures and strains of the work environment and evaluate their impact on employees’ health and safety and propose actions to improve health and safety at work. However, the changing working life and digitalization have increased the diversity of work, which is increasingly being done in virtual work communities. A digital workplace survey has become more common in occupational health services. The purpose of the study was to produce information about the digitized workplace survey in occupational health services. The study was conducted as a qualitative study during August to September 2019. The informants of the study (n=18) were occupational health professionals working in eight occupational health providers. The material was collected with group discussions (n=8), in which the themes were from the stages of the process of workplace survey in occupational health services and was analyzed using the content analysis method. Most commonly the digital workplace survey included a digital health and working conditions questionnaires for supervisors and employees, which produced a risk view with an individual and group levels. Some occupational health professionals used a digital platform, mainly for the management of workplace survey documents and communication with employers. The harmonization of digital surveys and better utilization of previous workplace surveys were mentioned as the development needs. Besides, the workplace survey reports should be displayed more visually to the workplaces. The digital workplace study is most often an electronic questionnaire. Although slight progress of technology has been made, it is necessary to continue the development of a digital workplace study process. Especially because technology makes it possible to find out about working conditions in a more versatile way. Also, on workplaces where occupational health professionals cannot be physically visited.